Analisis Perubahan Garis Pantai dengan Penginderaan Jauh di Kabupaten Badung, Bali Indonesia - Al Muqoddis, Gilang Maulana; Masitoh, Ferryati (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
This study aims to analyze shoreline changes in Badung Regency, Bali, over a seven-year period (2017-2023), using a remote sensing approach. The methods used involved the use of Sentinel-2 satellite image data, atmospheric correction, NDWI algorithm, raster to vector data conversion, and spatial analysis. The results showed the dominance of accretion over abrasion in the South Kuta area, influenced by factors such as ocean currents, bay geometry, and human activities. Shoreline shifts occur significantly in the westernmost segment, with minimal abrasion dynamics. Tidal conditions play an important role in sediment distribution and wave energy influencing shoreline changes. This study highlights the importance of long-term monitoring to plan appropriate mitigation and adaptation measures to shoreline change, with the results providing valuable insights for coastal area management and sustainable development in the South Kuta coastal area.